2002
DOI: 10.1021/ie0204540
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Pressure-Swing Adsorption Process Using Zeolite 13X for CO2 Sequestration

Abstract: A pressure-swing adsorption process, which uses zeolite 13X as an adsorbent to recover and sequester carbon dioxide from mixture gas (nitrogen and carbon dioxide), is investigated through dynamic simulation and optimization. The purpose of this paper is to improve the purity of each component by finding optimal values of decision variables with a given power constraint. Langmuir isotherm parameters are calculated from experimental data of zeolite 13X and a general mathematical model consisting of a set of part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
200
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(202 citation statements)
references
References 17 publications
(28 reference statements)
1
200
0
1
Order By: Relevance
“…The recovery of the PSA system is assumed to be 95% for CO 2 and 0% for any other gas of the mixture. 37,45 However, water vapor is present saturating the CO 2 , and it is absorbed too. Once the majority of CO 2 has been removed, the outlet of the PSA system can be fed to the reaction system or recycled back to the MEA system, to Mix 2, for the removal of H 2 S. Splitter 4 (Spl 4) determines the fraction of the stream coming out of the PSA system that follows each alternative.…”
Section: Co 2 and H 2 S Removalmentioning
confidence: 99%
“…The recovery of the PSA system is assumed to be 95% for CO 2 and 0% for any other gas of the mixture. 37,45 However, water vapor is present saturating the CO 2 , and it is absorbed too. Once the majority of CO 2 has been removed, the outlet of the PSA system can be fed to the reaction system or recycled back to the MEA system, to Mix 2, for the removal of H 2 S. Splitter 4 (Spl 4) determines the fraction of the stream coming out of the PSA system that follows each alternative.…”
Section: Co 2 and H 2 S Removalmentioning
confidence: 99%
“…For the selected cycle, all the step times, blowdown pressure, and flowrates of rinse and purge steps should be determined [25,[188][189][190][191][192]. Alternatively, it has been suggested that a general "super-cycle" can be used to estimate the optimal duration of each of the steps [193].…”
Section: Advances In Process Engineeringmentioning
confidence: 99%
“…Within TSA technologies, the specific case in which the solid is heated by the Joule effect is commonly referred to as electric swing adsorption (ESA) [5,6]. The vast majority of studies dealing with CO 2 post-combustion capture by means of PSA or TSA technologies use zeolites as adsorbent [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Zeolite 13X is by far the adsorbent most extensively studied in CO 2 separation processes, due to its high selectivity to CO 2 [21].…”
Section: Introductionmentioning
confidence: 99%